Rhomboid intercostal subserratus plane block – the Holy Grail of post-operative analgesia in modified radical mastectomy or just another dot in the long list? - Priyanka Bansal,; Nidhi Sultania,; Kunal Bansal, (Asian Journal of Medical Sciences, 2023)
Despite the presence of numerous options for breast analgesia, our women continue to suffer the consequences of acute post-operative pain that progresses to chronic pain in up to 55% of the post-mastectomy patients a rapid surge in the use of interfacial blocks for analgesia of chest and abdominal procedures. The importance and efficacy of these blocks are because of the continuity of the interfacial planes across varied anatomical tissues. We report a series of cases of modified radical mastectomy (MRM) in five female patients with the American Society of Anesthesiology Grade II/III in whom rhomboid intercostal subserratus was used for post-operative analgesia proved to be a boon. Two were post-radiation with metastasis to axillary lymph nodes. The other three had invasive ductal carcinoma and were on chemotherapy. Rhomboid intercostal subserratus plain block is a novel block and provides pain management for patients of MRM. The analgesic efficacy may not be superior but the non-inferiority to an epidural is certainly an added advantage with safe efficacious profile fulfilling the enhanced recovery after surgery protocols following minimally invasive surgical techniques.